2010
DOI: 10.1016/j.jesp.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of priming legal concepts on perceived trust and competitiveness, self-interested attitudes, and competitive behavior

Abstract: Socio-legal scholars have suggested that, as a ubiquitous social system, law shapes social reality and provides interpretive frameworks for social relations. Across 5 studies, we tested the idea that the law shapes social reality by fostering the assumptions that people are self-interested, untrustworthy, and competitive. In Studies 1 and 2, we found that people implicitly associated legal concepts with competitiveness. Studies 3 -5 showed that these associations had implications for social perceptions, self-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
3
16
1
Order By: Relevance
“…Empirical research on firm involvement in OSS communities confirms that a sponsor's trustworthiness impacts contributors' reported willingness to expend effort on the project Magnusson 2005, Dahlander andWallin 2006). This finding is consistent with the large body of work that draws connections between individuals' trust in others and their intrinsic desire to act cooperatively (Callan et al 2010).…”
Section: Credibilitysupporting
confidence: 66%
“…Empirical research on firm involvement in OSS communities confirms that a sponsor's trustworthiness impacts contributors' reported willingness to expend effort on the project Magnusson 2005, Dahlander andWallin 2006). This finding is consistent with the large body of work that draws connections between individuals' trust in others and their intrinsic desire to act cooperatively (Callan et al 2010).…”
Section: Credibilitysupporting
confidence: 66%
“…Callan et al. () have suggested that self‐interested and competitive attitudes will be stronger in legal conflicts than in conflicts that are not framed as legal. Others have shown the importance of voice and process control in legal proceedings (Houlden, LaTour, Walker, & Thibaut, ; LaTour, Houlden, Walker, & Thibaut, ; Tyler, Rasinski, & Spodick, ).…”
Section: Discussionmentioning
confidence: 99%
“…Justice researchers have primed people with concepts such as justice and morality (e.g., Callan, Kay, Olson, Brar & Whitefield, 2010), researchers on terror management theory primed participants with thoughts of death (see Vail et al, 2012, for a recent review), colleagues interested in religion primed people with God (e.g., Gervais & Norenzayan, 2012), psychologists interested in group behavior primed identity (e.g., Levine, Cassidy, & Jentzsch, 2010), and literally dozens of papers have reported effects of priming people with power (e.g., Galinsky, Gruenfeld, & Magee, 2003;Smith & Trope, 2006;Yap, Mason, & Ames, 2012). Many people may not classify this research as examples of behavior priming, but in our view they are.…”
Section: A Large Amount Of Evidencementioning
confidence: 99%